"This Is Not A Rule": COVID-19 in England & Wales and Criminal Justice Governance via Guidance. (9th March 2021) - SORABJI, John; VAUGHAN, Steven
Abstract : While soft law is an integral part of the efficient and effective functioning of public administration in England & Wales, the extent to which it was deployed in response to COVID-19 is striking, with over 400 pieces of "guidance and regulations" created. In this article, we consider the general place of soft law in administrative law in England & Wales and the broad regulatory framework, including soft law, that governs the COVID-19 pandemic. This allows us to take a deep dive into COVID-19 and the criminal justice system, showing how the senior judiciary relied predominately on soft law (judicial guidance and protocols) to manage the system (set against the backdrop of targeted legislation and a limited number of Practice Directions, which have the force of law). We argue that the senior judiciary's approach to the use of COVID-19 soft law has, in many ways, been more effective than that taken by the government. Yet there remains room for improvement, particularly in the nature of the judicial guidance issued and about what guidance was in place and when.